Extraurogenitálne dôkazy Chlamydia trachomatis--perinatálny prenos - Cisláková, L; Pospisil, R; Holler, J; Várady, L; Prokopcáková, H; Peterková, J (Epidemiologie, mikrobiologie, imunologie, 1994)
Infections produced by Chlamydia trachomatis reach an epidemic scale worldwide. Examination of 1,333 women with suspected cervicitis and other clinical symptoms revealed positive findings in 355 (27.5%). Of 72 examined men 25 (34.7%) were positive. Perinatal infection is confirmed also by positive evidence of Ch. t. in 28.9% neonates with conjunctivitis and 19% positive smears from the nasopharynx. The authors used the direct immunofluorescent method, Chlamyset of Orion Co., Finland.
Keywords: Chlamydia trachomatis; Conjunctivitis, Bacterial; mužské pohlaví; cervix uteri; Chlamydia Infections; Infectious Disease Transmission, Vertical; Infant, Newborn; ženské pohlaví; novorozenec; Humans; vertikální přenos infekce; ureter; bakteriální konjunktivitida; Female; Ureter; chlamydiové infekce; Cervix Uteri; lidé; Male